Cooperation of vocational colleges and enterprises in China: Institutional foundations of vocational education and skill formation in nursing and mechanical engineering - Preliminary findings - Armin Müller (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
In the context of the ongoing transformation of China's economic development model, the central government under Xi Jinping announced a general upgrading of China's skill-formation system. The initiative is part of a larger strategy to avoid the middle income trap and move towards a high-skill route of development. One of the core challenges in this respect is to consolidate the cooperation of enterprises and vocational schools and colleges, and to couple the realms of education and employment more tightly. The aim of this paper is to analyze these issues in the institutional context of state-permeated capitalism from the perspective of actor-centered institutionalism. By conducting a structured and focused comparison of the fields of nursing and mechanical engineering in two vocational colleges in Eastern China, it identifies important factors facilitative to reforms. The nursing case illustrates that bureaucratic integration and a dominance of the public sector facilitate the cooperation of schools and enterprises and the coupling of education and employment. Here, hierarchical steering can reinforce cooperation and couple education and employment via vocational qualification certificates. The fragmentation of bureaucratic authority and marketization, on the other hand, require new patterns of cooperation and coupling. The case of mechanical engineering illustrates the potential of well-performing education facilities to attract cooperation partners without direct state support, and of industry associations to play an intermediary role between schools and companies, and to develop new vocational qualifications geared to companies' requirements. The case study design focuses on areas of vocational education with high incentives for cooperation and good material conditions. The preliminary results indicate that the generally negative assessment of China's TVET system in the literature may be somewhat too pessimistic, and that a more differentiated analysis is needed.
Keywords: 330; China; vocational education; vocational colleges; skill formation; nursing; mechanical engineering